2016
DOI: 10.1073/pnas.1525130113
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the mechanisms behind climate effects on zooplankton

Abstract: Understanding how climate influences ecosystems is complicated by the many correlated and interrelated impacting factors. Here we quantify climate effects on Calanus finmarchicus in the northeastern Norwegian Sea and southwestern Barents Sea. By combining oceanographic drift models and statistical analyses of field data from 1959 to 1993 and investigating effects across trophic levels, we are able to elucidate pathways by which climate influences zooplankton. The results show that both chlorophyll biomass in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Amaral et al (2017) and Leite et al (2009) found a high diversity of this species along the Brazilian coast, indicating it is independent of seasonality since it tends to reproduce whenever it finds favorable oceanographic characteristics. The copepod nauplii identified in the study by Kvilea et al (2016) were strongly influenced by physical-chemical parameters such as surface water temperature, which corroborates the results found in the São Luís and São José de Ribamar tide-control structures, through canonical correspondence analysis (CCA).…”
Section: Discussionsupporting
confidence: 86%
“…Amaral et al (2017) and Leite et al (2009) found a high diversity of this species along the Brazilian coast, indicating it is independent of seasonality since it tends to reproduce whenever it finds favorable oceanographic characteristics. The copepod nauplii identified in the study by Kvilea et al (2016) were strongly influenced by physical-chemical parameters such as surface water temperature, which corroborates the results found in the São Luís and São José de Ribamar tide-control structures, through canonical correspondence analysis (CCA).…”
Section: Discussionsupporting
confidence: 86%
“…Understanding and predicting responses of planktonic communities to the changing physical and biological environments from a pan‐Arctic perspective is very challenging because few long‐term, high‐frequency, and broad spatial coverage observations from the extreme Arctic Ocean exist [ Wassmann , ]. Marine ecological models, particularly individual‐based models (IBMs) that deal with organisms at the individual level and account for individuals' life history and/or behaviors, have proven to be useful tools in explaining observed biogeographic and ecological patterns across the entire Arctic Ocean [e.g., Ji et al ., ] or in specific Arctic/subarctic seas [e.g., Berline et al ., ; Maps et al ., ; Hjøllo et al ., ; Elliott , ; Kvile et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…How changes in sea surface temperature may influence marine organisms, especially ectotherms (Pinsky et al, 2019) such as fishes (Moyano et al 2017;Dahlke et al, 2020) and zooplankton (Edwards and Richardson, 2004;Kvile et al, 2016), has been one of the key focuses of research efforts over the past two decades. Whilst numerous studies have now examined temperature effects on jellyfish and especially on polyps (Shi et al, 2018;Purcell et al, 2012;Lu et al, 2020), none have examined potential interactions between temperature and duration of temperature on strobilation.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal windows constrain ectothermic animal distributions and limit the geographic range within which they can live and reproduce (Höhn et al, 2017;Dahlke et al, 2020). Each population's thermal window differs and this may contribute to the population-specific timings of reproduction, and to their variable responses to different minimum winter temperatures (Kroiher et al, 2000;Pascual et al, 2015;Kvile et al, 2016). Some studies report that warmer temperatures result in more ephyrae (e.g.…”
Section: Discussionmentioning
confidence: 99%